The Rancang Bangun Aplikasi Pendataan Proyek Konstruksi Berbasis Web Menggunakan Metode Waterfall : Bahasa Indonesia - Khalimin; Thomas Budiman; Anton Zulkarnain Sianipar (POSITIF : Jurnal Sistem dan Teknologi Informasi, 2026)
Construction project data management at PT. Reynolds Partnership is still conducted manually using Microsoft Excel, which may result in data duplication, recording errors, and difficulties in accessing information. To address these issues, a web-based project data management application was designed using the waterfall methodology. The application was developed with the PHP programming language and a MySQL database, and it supports five user roles: admin, associate, team leader, quantity surveyor, and project administrator. The study results indicate that this web-based application can improve work efficiency, minimize data errors, and support the decision-making process. It is expected that the application will enhance the effectiveness and efficiency of project data management at PT. Reynolds Partnership.